Exchange Rate Dynamics Redux - Obstfeld, Maurice; Rogoff, Kenneth (Journal of Political Economy, 1995)
We develop an analytically tractable two-country model that marries a full account of global macroeconomic dynamics to a supply framework based on monopolistic competition and sticky nominal prices. The model offers simple and intuitive predictions about exchange rates and current accounts that sometimes differ sharply from those of either modern flexible-price intertemporal models or traditional sticky-price Keynesian models. Our analysis leads to a novel perspective on the international welfare spillovers due to monetary and fiscal policies.